Measurement of the tt̄ production cross section in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2008)
We measure the tt̄ production cross section in pp̄ collisions at s=1.96TeV in the lepton+jets channel. Two complementary methods discriminate between signal and background: b tagging and a kinematic likelihood discriminant. Based on 0.9fb-1 of data collected by the D0 detector at the Fermilab Tevatron Collider, we measure σtt̄=7.62±0.85pb, assuming the current world average mt=172.6GeV. We compare our cross section measurement with theory predictions to determine a value for the top-quark mass of 170±7GeV. © 2008 The American Physical Society.